The Importance Of Motor Analysis In The Exercise Of Motor Skills And In Improving Performance - Barkati, Nasereddin (sports creativity, 2025)
This study aimed to identify the importance of kinematic analysis in improving and developing athletic performance. It also aimed to identify the relationship between kinematic variables among the sample members in improving performance, as well as the relationship between the study members in the athletic achievement process. The study was conducted on a purposive sample of 20 third-year LMD (License-Master-Doctorate) students, divided equally into two groups: an experimental group and a control group of 10 students each. A long jump training program (specific to the experimental group) was implemented, during which the participants in both groups were filmed. The researcher employed the experimental method and used the X-Kenova kinematic analysis software for data collection. A performance evaluation observation checklist was used to collect data. The study concluded that there is a relationship between biomechanical variables between the two groups, favoring the experimental group. A non-significant difference in stride length was also found between the two groups. Furthermore, a relationship was established between kinematic variables and improved performance. The study demonstrated the importance of kinematic analysis in revealing the relationship between performance and kinematic variables in the achievement process. It recommends further research into kinematic analysis. The researcher stressed the importance of studying the kinematic variables and improving the technical performance of the long jump event, as well as conducting special studies for various other events in athletics.